Representações da cultura brasileira contemporânea em materiais didáticos de PLE - Figueiredo, Adriana Pinto (2009)
This study examines the way Brazilian contemporary culture is approached in the teaching of Portuguese as a Foreign Language, through the analysis of cultural components from coursebooks edited in Brazil. It was researched, among the materials published in the last two decades, a group of textbooks by the same authors and directed to similar kinds of public, so that the selection and approach of their cultural components could be compared.The evaluation of the samples selected from these materials revealed the beginning of a process in which their cultural components are approached in accordance with paradigms established in recent theories of cultural representation.These theories have been generated since the 90´s, in the context of the so called latest period of globalization.